Sensitivity on stock returns and volatility: the case of Shari’ah-compliant securities in Bursa Malaysia / Roslina Mohamad Shaft - Shaft, Roslina Mohamad (2011)
The introduction of the shari'ah-compliant securities by the SAC in the stock market has gained attention among the Muslim investors. Whether SAC announcements on shari'ah-compliant securities are a source of the abnormal returns and volatility of securities is the focus of this study. Hence, statistical evidence needs to be discovered in order to know the significance of the event of SAC announcements on the shari'ah-compliant securities. Data on MCARs for each addition/deletion announcements and volatility by subsamples partitioning is used. Then, the Event Study methodology was applied for each subsample. It was found that there were no significant abnormal returns on the securities prices before and after the announcements. As for the volatility, the addition of securities partitioned by market directions shows that MCARs are positive while deletion is negative when the market is up. For the volatility market subsamples, it was found that investors underreact to good news during low volatility market and over-react to bad news during low volatility market. It can be said that market efficiency is anomalous. Although the results and analysis may provide the beginning of a more complete understanding of the puzzling returns of common stock surrounding the shari 'ah-compliant securities addition and deletion, the phenomenon deserves further investigation.